The Utilization of Crude Glycerol with Low Methanol Content on Production Performance and Blood Chemistry of Laying Hens - Pinchai, Benjawan; Songserm, Ornprapun; Ruangpanit, Yuwares (Journal of Mahanakorn Veterinary Medicine, 2021)
The experiment was conducted to determine the utilization of crude glycerol with low methanol content on production performance and blood chemistry of laying hens. A total of 480 laying hen, 32 WOA H&N Brown were divided into 4 dietary treatments (8 replications with 15 birds each) including 0, 2.5, 5 and 7.5 % crude glycerol respectively. Production performance was recorded for 4-4 weeks periods (a total of 16 weeks). Egg quality measurement was performed for the last 3 consecutive days of each period. Blood chemistry was analyzed at the end of period 2. There was no significant difference on production performance and egg quality among dietary treatments (P>0.05). However, using crude glycerol ≥ 5 % decreased average feed intake of laying hen (P<0.01). The use of crude glycerol at 7.5 % decreased eggshell thickness, % eggshell weight and yolk color (P<0.05). An increase in the level of crude glycerol in the diet numerically increased blood glycerol (P=0.2751) and significantly increased the level of blood glucose (P<0.05). From the present study, crude glycerol could be incorporated in laying hens diets up to 7.5 % without causing any negative effect of egg production and egg quality. However, the levels of sodium chloride in crude glycerol should be using to formulate the diet to obtain suitable levels of sodium chloride in the diets to prevent negative effect of excess sodium chloride in the diets.